Regulation of Public Finances in Slovakia in Light of Financial Constitutionality - Štrkolec, Miroslav (Regulation of Public Finances in Light of Financial Constitutionality: Analysis on Certain Central and Eastern European Countries, 2022)
This chapter is devoted to the foundations of financial law and financial regulation in Slovakia. Its aim is to define financial law in the system of law in Slovakia and to specify the basic areas of its regulation. In the introduction, it discusses the theoretical background of financial law as a branch of law and its relations to other branches of law. Then, building on the Constitution of the Slovak Republic, it defines the basic areas of its regulation—budgets, taxes and fees, currency, customs, and the financial market. In relation to all these areas, the aim is to specify their constitutional regulation and, consequently, the basic parametres of legal regulation. The aim is to give a basic overview of financial law instruments and concepts in Slovakia, such as the state budget and local budgets, state taxes and local taxes, customs, currency in the context of the monetary union, and financial market entities and instruments. However, the ambition is also to define the basic framework of the most important financial authorities and institutions in Slovakia, such as the Ministry of Finance of the Slovak Republic, the Supreme Audit Office, the National Bank of Slovakia, and the Council for Budget Responsibility. The conclusion will not only offer a summary, but will also highlight the most important current regulatory challenges for financial law, which are related to the COVID-19 pandemic, as well as to the digital transformation. KEYWORDS: Financial law, budget, tax, customs, currency, financial market.